2006
DOI: 10.1002/hon.802
|View full text |Cite
|
Sign up to set email alerts
|

Fertility among female hodgkin lymphoma survivors attempting pregnancy following ABVD chemotherapy

Abstract: Although ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) chemotherapy is infrequently associated with premature amenorrhea, little is known about the success rate of women attempting pregnancy following ABVD. In the present study females treated for HL with ABVD chemotherapy without pelvic radiation therapy (RT) and who were alive without relapse > or =3 years after treatment were identified from a clinical database and screened for inclusion. Using a standardized questionnaire, we determined the pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 30 publications
1
74
0
1
Order By: Relevance
“…It is striking that four out of five reported successful pregnancies were in patients with lymphomas, and data on cryopreservation in an extensive series of such patients have recently been published (Meirow et al 2007). Treatment regimens for lymphoma may be less gonadotoxic in women than previously (Clark et al 1995, Hodgson et al 2007, whereas the increasing use of taxanes in, for example, breast cancer may be associated with increased gonadotoxicity .…”
Section: Patient Outcomesmentioning
confidence: 99%
“…It is striking that four out of five reported successful pregnancies were in patients with lymphomas, and data on cryopreservation in an extensive series of such patients have recently been published (Meirow et al 2007). Treatment regimens for lymphoma may be less gonadotoxic in women than previously (Clark et al 1995, Hodgson et al 2007, whereas the increasing use of taxanes in, for example, breast cancer may be associated with increased gonadotoxicity .…”
Section: Patient Outcomesmentioning
confidence: 99%
“…with a high incidence of ovarian toxicity, while regimens such as doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) are associated with less risk [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of achieved pregnancies and childbirths is sometimes reported in small series (Schilsky et al, 1981;Whitehead et al, 1983;Bonadonna et al, 1984;Anselmo et al, 1990), the selection of survivors attempting parenthood is not reported, with a few exceptions (Aisner et al, 1993;Hodgson et al, 2006).…”
mentioning
confidence: 99%